The Concept of Moral Education from The Perspective of Syaikh Muhammad Syakir and Umar Bin Ahmad Baraja - Haryanto, Haryanto (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This research aims to analyze the concept of moral education according to Syaikh Muhammad Syakir compared with the concept of moral education of Shaykh Umar BinAhmad Baraja in the book Washoya al-aba’ lil abna and books Al-Akhlak Lil Banin. This research method uses a qualitative method with this type of research using the character study method. This research found that the concept of moral education for Syaikh Muhammad Syakir in his book includes several concepts, namely: the concept of morals towards Allah and His Messenger, the concept of morals towards oneself, the concept of morals towards parents, teachers and friends, as well as the concept of morals towards other people and society, while the concept of moral education of Syaikh Umar Bin Ahmad Baraja in his book includes several concepts, namely: beloved students, students' morals before going to school, students' morals on the journey, students' morals in school, students' morals in maintaining school equipment, students' morals towards teachers, and students' morals towards friends.